Modified Leak-Proof Puncture Technique for the Aspiration of Giant Ovarian Cysts by Instantly Mounting a Plastic Wrap and Gauze with Cyanoacrylates: A Retrospective Observational Study - Ishikawa, Hiroshi; Shozu, Makio (Frontiers in Surgery, 2022)
Objective: We developed a leak-proof puncture technique for giant ovarian cysts by instantly mounting a plastic wrap to the cysts using cyanoacrylates and aspirating cyst fluid over the wrap. Here, we modified it by inserting a gauze between the wrap and cyst to strengthen the mounting. This study aimed to clarify the feasibility of the modified procedure. Method: A retrospective observational study was conducted in a single center. Surgical outcomes of 35 women who underwent the modified procedure from December 2013 to July 2020 were compared with those of 51 women who underwent the original procedure. Results: Mean long-axis diameters of the cysts were 233.1 mm and 229.8 mm in the modified and original procedures, respectively. The median of surgical time, blood loss, and aspirated fluid volume were 109 min, 50 mL, and 3,050 mL, in the modified procedure, all of which were not significantly different from those of the original procedure. One case of mounting disruption and two (5.7%) cases of intraperitoneal spillage of the cyst fluid were observed in the modified procedure, whereas four (7.8%) cases of mounting disruption and five (9.8%) cases of intraperitoneal spillage occurred in the original procedure. These events were caused by aspiration difficulty of the high viscosity fluid and/or multilocular cysts. Laparotomy conversion was observed in five (14.3%) cases in the modified procedure. Conclusion: Our modified procedure is feasible in select cases. The high viscosity of the cyst fluid and multilocular cyst may cause mounting disruption and intraperitoneal spillage of the cyst fluid.